FTIR Spectrophotometry as a Green Tool for Quantitative Analysis of Drugs: Practical Application to Amoxicillin - Stefany Fanelli; Alexander Zimmermann; Eliane Gandolpho Totóli; Hérida Regina Nunes Salgado (Journal of Chemistry)
Amoxicillin is an antimicrobial agent that belongs to the penicillin compounds. Its bactericidal action causes a destruction of the cell wall of bacteria. It is widely used in clinical practice, and it belongs to the Brazilian National List of Essential Drugs (RENAME). In literature, there are some green analytical methods for the amoxicillin analysis; however, none of them is focused on its quantification in capsules. Therefore, the aim of this study was to validate an environmentally friendly analytical method for the analysis of this antimicrobial action in capsules, using spectrophotometry in the mid-infrared region. The analyses were performed in the spectral range of 1815–1736 cm−1, and the samples were analyzed as potassium bromide pellets. The method was validated according to the ICH guidelines and Brazilian legislation. Linearity, selectivity, precision, accuracy, and robustness were evaluated and showed adequate results for method validation, in a concentration range of 0.5–1.5 mg/pellet. Thus, it is concluded that the validated spectrophotometric method is able to quantify amoxicillin in capsules. In addition, it is a fast, economical, and environmentally friendly method, since it does not use organic solvents, and it can be used for quality control of routine analysis of this drug.